Bacillus subtilis na qualidade dos pintinhos ao nascer, desempenho e características intestinais dos frangos - Borges, Liliana Longo [UNESP] (2015)
A study was conducted to verify the effect of in ovo inoculation of Bacillus subtilis and feed supplementation during the creation, on the morphological and morphometric characteristics of the small intestine, performance and carcass yield of broilers. The study consisted of two experiments. In the first 500 fertile chicken eggs over five horizontal incubators were used. The experimental design was randomized blocks, each considered as a block incubator, with five treatments (control, NaCl, CFU 106, CFU 107, CFU 108), and 100 eggs/treatment. At 18 days of incubation the eggs were inoculated with the solutions in the air cell and the hatch were evaluated for quantification and identification of Bacillus subtilis in the intestinal mucosa, hatchability of fertile eggs, total rate of hatching, embryo mortality and chick quality, birth weight and weights of the intestine, liver and yolk sac of male chicks. The concentration 107 provided better results relative to hatchability and chick weight at birth. In the second experiment in 2700 fertile eggs were incubated in an incubator CASP single stage. At 18 days of incubation 1350 eggs were inoculated with 107 CFU Bacillus and 1350 eggs remained without inoculation. When the hatch in the shed males were housed according to the treatment. The design was a randomized block design with a 2x2 factorial design (in ovo inoculation of Bacillus subtilis or not X supplementation of Bacillus subtilis in the creation phase or not), with six replicates of 35 birds each, totaling 840 birds. Were analyzed the morphometry of the small intestine, the weights of the liver, intestine and pancreas at one, four, eight, 13, 20 and 41 days of age, the results at 21 and 42 days of age, performance at 21 and 42 days of age, carcass yield and cuts, and meat quality at 42 days of age. The in ovo inoculation of Bacillus subtilis and feed supplementation promoted best results for depths length of villi and crypts in ...